True exposure: The analytics of trade liberalization in a general equilibrium framework - Friedrich L. Sell (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1988)
These is an ongoing debate with regard to the Timing and Sequencing of Liberalization in LDC's. The Capital Account or Trade Account First'-Puzzle is tackled with different methodological tools of analysis, ranging from the Political Economy Approach put forward by D. Lai (1987) to the orthodox Price and Resource Movement Analysis by S. Edwards (1986). D. Lai favours a sequencing in which exchange controls are removed first, introducing a free floating exchange rate, and a phased program of trade liberalization should follow. If, instead, trade liberalization is accompanied by a managed exchange rate system requiring capital controls, the real exchange rate will be affected severely by the nominal exchange rates chosen by the government. These choices, in turn, will seldom correspond to the economic requirements as reflected in the balance of payments. When deficits occur, governments may then be tempted to impose new trade controls - thus aborting the trade liberalization (Lai 1987, p. 290). S. Edwards, on the other hand, comes to the conclusion that both types of liberalization, on their own, generate by tendency opposite effects on prices, production, factor allocation and income distribution. As resource movements are not for free, net reallocation costs can be minimized by synchronising the opening of the capital and current accounts. However, given the fact that the capital account tends to adjust faster than the current account, the synchronization of the economic effects of opening both accounts will require that the current account is opened first (Edwards 1986, p. 210).
Keywords: 330; Außenhandelsliberalisierung; Theorie; Entwicklungsländer